After Prophecy, Wisdom? Matrices and Legacies of Liberation Theology - Francys Silvestrini Adão (Religions, 2025)
The aim of this article is to explain the sapiential moment experienced by some Latin American theologies and, in relation to it, the possible emergence of a new look at the origins of the liberation movements of the last century. Firstly, an interpretation of the ethical–spiritual matrix of liberation theologies and the affiliations that have sprung from this experience is summarily presented. Next, an example of the sapiential heirs of Latin American liberation theologies is shown: theogastronomy. Thirdly, a new hypothesis is proposed about the ethical–spiritual matrix presented above, associating it with the women’s emancipation movement. Finally, it concludes with a brief Eucharistic reflection, which gives a paschal meaning to the rereading presented, opening prospects for reconciliation in the contemporary world.